Assessment of knowledge, attitudes, and performance of postgraduate nursing students regarding clinical reasoning and evidence-based nursing: a multicenter cross-sectional study in Iran - Zahra Mohebi; Azizallah Dehghan; Ali Taghinezhad; Sorur Javanmardifard; Mostafa Bijani (BMC Nursing)
Abstract Background Within the realm of medical education, particularly in nursing, the paramount objective is to cultivate professionals who can make optimal clinical decisions through the integration of critical thinking skills, comprehensive knowledge, clinical reasoning, and evidence-based nursing practices. Given that these professional competencies constitute the cornerstone of effective healthcare delivery; their systematic development has become increasingly imperative. This study, therefore, aims to evaluate postgraduate nursing students’ knowledge, attitudes, and performance regarding clinical reasoning and evidence-based nursing. Methods A descriptive cross-sectional multicenter study was undertaken from September through November 2024. The study population comprised postgraduate nursing students from three medical sciences universities in Fars Province, Southern Iran. Through convenience sampling, 165 postgraduate nursing students were enrolled in the study. Data collection was accomplished using two validated questionnaires specifically designed to assess attitudes, knowledge, and performance in clinical reasoning and evidence-based nursing. The comprehensive assessment instrument incorporated three components for clinical reasoning: Clinical Reasoning Attitude (CR-A), Clinical Reasoning Knowledge (CR-K), and Clinical Reasoning Practice (CR-P). Additionally, it included three parallel components for evidence-based nursing: Evidence-Based Nursing Attitude (EBN-A), Evidence-Based Nursing Knowledge (EBN-K), and Evidence-Based Nursing Practice (EBN-P). Statistical analyses were performed using chi-square tests, Kolmogorov-Smirnov test, Pearson correlation coefficients, multiple linear regression with statistical significance established at p < 0.05. All analyses were conducted using SPSS version 25. Results Of the 165 eligible postgraduate nursing students who participated in this study, 134 (81.2%) were master’s degree students, and 31 (18.8%) were doctoral candidates. The mean age of the participants was 31.16 ± 5.25 years. Among the three components of clinical reasoning examined, the mean scores were 0.75 for CR-K, 0.88 for CR-A, and 0.56 for CR-P, all of which fell within the satisfactory range. Similarly, the evidence-based nursing components yielded mean scores of 0.49 for EBN-K, 0.87 for EBN-A, and 0.55 for EBN-P, which, consistent with the clinical reasoning scores, were all within the satisfactory range. Furthermore, doctoral students demonstrated significantly higher mean scores across all components compared with master’s students in both domains. The results of multiple linear regression models showed a direct and statistically significant relationship among evidence-based nursing practice (EBN-P), with Evidence-Based Nursing Attitude (EBN-A), β = 0.462, p < 0.001) and Evidence-Based Nursing knowledge (EBN-K), β = 0.018, p < 0.001) and Educational level (β = 0.204, p < 0.05). The results of multiple linear regression models showed a direct and statistically significant relationship between clinical reasoning practice (CR-P) with clinical reasoning knowledge(CR-K), β = 0.164, p < 0.05) and clinical reasoning attitude (CR-A), β = 0.118 p < 0.001) and Educational level (β = 0.354, p < 0.001). Conclusion The findings of this empirical investigation revealed that postgraduate students across both master’s and doctoral programs demonstrated exceptionally favorable mean scores in all three components of clinical reasoning and evidence-based nursing: knowledge, attitude, and practice. Of particular significance was the observation that doctoral students consistently achieved substantially higher mean scores across these components compared to their counterparts in master’s programs. The findings from this investigation offer valuable implications for nursing education administrators in their ongoing efforts to enhance educational outcomes. These results provide a robust framework through which administrators can systematically evaluate nursing students’ knowledge, attitudes, and performance in both clinical reasoning and evidence-based nursing practice.